2001
DOI: 10.1002/dmrr.185
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion, obesity, and potential behavioral influences: results from the Insulin Resistance Atherosclerosis Study (IRAS)

Abstract: Among non-diabetic patients, central obesity appears to be related to higher insulin secretion, but to lower capacity of the pancreas to respond to the ambient insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
4
14
1
Order By: Relevance
“…The biological mechanism underlying the association between MetS and ␤-cell dysfunction may be related to the fact that a number of MetS components, including elevated abdominal obesity and triglyceride concentration and reduced HDL levels, are strongly correlated with elevated circulating concentrations of free fatty acids (47), chronic elevations of which are known to be associated with lipotoxic damage to the pancreatic ␤-cells (48). This hypothesis is consistent with results from a previous study using IRAS data, in which it was reported that elevated waist circumference was significantly associated with reduced DI (49). The notably strong association of NCEPMetS with reduced IS among blacks suggests the possibility that NCEP-MetS may be an especially useful predictor of diabetes in this ethnic group.…”
Section: Discussionsupporting
confidence: 92%
“…The biological mechanism underlying the association between MetS and ␤-cell dysfunction may be related to the fact that a number of MetS components, including elevated abdominal obesity and triglyceride concentration and reduced HDL levels, are strongly correlated with elevated circulating concentrations of free fatty acids (47), chronic elevations of which are known to be associated with lipotoxic damage to the pancreatic ␤-cells (48). This hypothesis is consistent with results from a previous study using IRAS data, in which it was reported that elevated waist circumference was significantly associated with reduced DI (49). The notably strong association of NCEPMetS with reduced IS among blacks suggests the possibility that NCEP-MetS may be an especially useful predictor of diabetes in this ethnic group.…”
Section: Discussionsupporting
confidence: 92%
“…No association of glycemic index, glycemic load, or carbohydrates was observed with AIR or disposition index. Previous work in our population on alcohol intake, fat intake, and physical activity similarly reported no impact of these behavioral factors on AIR or disposition index (31). A recent intervention study, however, observed a significant improvement in disposition index among individuals with impaired glucose tolerance randomized to a high-carbohydrate, low-glycemic index diet (32).…”
Section: Discussionmentioning
confidence: 58%
“…In the IRAS, dietary fat intake was positively related to insulin secretion, measured by the minimal model, in subjects with normal glucose tolerance but not in those with impaired glucose tolerance (28). In contrast, a study by Larsson et al (29) did not find any correlation between intake of specific dietary fatty acids and insulin secretory response to arginine in postmenopausal women.…”
Section: Methodsmentioning
confidence: 82%